2022
DOI: 10.18632/aging.204100
|View full text |Cite
|
Sign up to set email alerts
|

Lactotransferrin promotes intervertebral disc degeneration by regulating Fas and inhibiting human nucleus pulposus cell apoptosis

Abstract: Background: In recent years, intervertebral disc (IVD) degeneration (IDD) has increased in age. There is still a lack of effective treatment in clinics, which cannot improve the condition of IDD at the level of etiology. Objective: To explore IDD pathogenesis at the cellular and gene levels and investigate lactotransferrin (LTF) expression in IDD patients and its possible mechanism. Methods: We downloaded the IDD data set from the Gene Expression Omnibus (GEO) database, screened the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Various studies have reported that excessive activation of NF-κB could induce the progression of nearly all aging-related diseases, and inhibition of NF-κB, in contrast, could reverse SASP and aging ( García-García et al, 2021 ; Zhang X. B. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported that excessive activation of NF-κB could induce the progression of nearly all aging-related diseases, and inhibition of NF-κB, in contrast, could reverse SASP and aging ( García-García et al, 2021 ; Zhang X. B. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%